Adjudicating family law in Muslim courts - Giunchi, Elisa (Abingdon, Oxon : Routledge, 2014)
'While there are many books on Islamic family law, the literature on its enforcement is scarce. This book focuses on how Islamic family law is interpreted and applied by judges in a range of Muslim countries, Sunni and Shi'a, as well as Arab and non-Arab. It thereby aids the understanding of shari'a law in practice in a number of different cultural and political settings. It shows how the existence of differing views of what shari'a is, as well as the presence of a vast body of legal material which judges can refer to, make it possible for courts to interpret Islamic law in creative and innovative ways'--
Includes bibliographical references and index.
Keywords: Domestic relations (Islamic law); Domestic relations -- Islamic countries